Definition of coded current of automated lokomotive signalization within central location of automated blocking system - Romantsev, I. O. (Science and Transport Progress, 2012)
The mathematic model and telemeasuring method of definition of automated locomotive signalization current is offered, that simplifies and allows to automatize the process of his determination, at the centralized placing of apparatus of the automatic blocking.